Natural Gas: A Source of Alternative Energy - Yenque Dedios, Julio (2000)
In a world in which oil reserves are consumed rapidly, the alternative of using natural gas is presented as the best solution. a great alternative solution to the energy problem in Peru that has large reserves of natural gas and Aguaytía Camisea, which could become, in the short term; as the best source of energy.